Influence of Market Orientation, Learning Orientation, and Innovation Capabilities and Their Impact on Competitive Advantage and Company Performance - Dwi Hari Laksana; Satya Apriliado; Titik Kusmantini (Journal of The Community Development in Asia, 2022)
ABSTRACTÂ To meet the needs of heterogeneous consumers, companies must be market-oriented and innovate to advance company performance. This research will analyze the influence of market orientation, learning orientation, innovation capabilities, and their impact on competitive advantage and company performance in Ngelorejo bamboo craft center, Gunung Kidul district, Indonesia. In the collection of data, this study used questionnaires with the number of respondents as many as 88 respondents bamboo artisans. The analysis method used is Structural Equation Modeling (SEM) and the analysis tool used is Smart PLS 3.0. The results of this study showed that market orientation has a significant effect on innovation capabilities, learning orientation has a significant effect on innovation capabilities, market orientation has no significant effect on competitive advantage, market orientation has a significant effect on company performance, innovation capability has a significant effect on competitive advantage, a competitive advantage does not have a significant effect on company performance.Keywords: Market orientation, Learning orientation, innovation capabilities, Competitive advantages, Company performance. Â